TRANSPORT OF PATIENTS FOR PRIMARY PTCA FROM GENERAL HOSPITAL NOVO MESTO TO LJUBLJANA - Renata Okrajšek (Zdravniški Vestnik, 2003)
Background. The treatment of acute coronary syndrom (ACS) with ST-segment elevation with primary percutaneous transluminal coronary angioplasty (PTCA) has been a routine method for treatment of these patients in KC Ljubljana since April 2000. Using this method, mortality due to ACS, reinfarction, total number of death and strokes in comparison to thrombolytic therapy were highly reduced. Since May 2001 primary PTCA has been attainable also for patients from regional hospitals to be transferred quickly enough to Ljubljana. Methods. A retrospective analysis of patients with ACS with ST-segment elevation who have been transferred from General Hospital Novo mesto to KC Ljubljana in the period from Oct. 1, 2001 to March 31, 2002 to have a primary PTCA was performed. The analysis comprised the following: time interval from the chest pain start to the arrival of patient to the General Hospital Novo mesto, handling of patient at Internistic department of General Hospital Novo mesto, transport of patient to Ljubljana and total time interval from the arrival of patient to the first inflation of balloon in Ljubljana. Results. In the upper mentioned period 14 patient (12 males and 2 females) were transported from the General Hospital Novo mesto to the KC Ljubljana to perform a primary PTCA. Our patients arrive to hospital very late. Due to problems with transport organisation and patient’s escort and duty, total time interval measured between the patient arrival to the General Hospital Novo mesto to the first inflation of balloon in Ljubljana was 2h and 42 minutes. That was longer that had been stated previously in the literature. Conclusions. In our opinion, primary PTCA is practicable also for patients admitted to a regional hospital because of ACS with ST-segment elevation. The transport of patient is safe. Better organisation of Health Service and patient transportion would shorten the time needed to perform the first inflation of balloon in Ljubljana.